Spontaneous Carotid-Cavernous Fistula and Subarachnoid Hemorrhage - Damelan, Kombate; Kokou Mensah, Guinhouya; kossivi kumako vinyo, Apetse; mofou, Belo; agnon ayélola koffi, Balogou (Journal of Neurological Research And Therapy, 2016)
Carotid-cavernous fistula (CCF) is a rare neurological condition with risk of death in case of inappropriate management. The outcome of this pathology is very bad in developing countries with inadequate technical Platform. We underlined the main difficulties of the management of CCF in a 43 years-old Togolese woman with a fatal outcome.
Keywords: carotid-cavernous fistula; fatal outcome; interventional neuroradiology